2022
DOI: 10.3390/jrfm15110536
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Personality Traits, Digital Technology Skills and Competency on the Effectiveness of Fraud Risk Assessment among External Auditors

Abstract: In accordance with ISA 240, it is the responsibility of external auditors to obtain reasonable assurance that financial statements are free from material misstatement, whether caused by fraud or error. Recently, the auditing profession in Malaysia has been significantly challenged by the explosion of fraud cases and by auditors’ failure to determine the “true and fair view” of the financial statement. This incident has tarnished the reputation of the audit profession. The effectiveness of the external auditor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…The study [33] uses the number of compromised records to determine the cost of a data breach; the findings indicate that the total number of affected records has a Fréchet distribution, random forest is used for estimating the number of such records. The study [34] uses the estimate of generalized extreme value parameters to evaluates competency, digital technology abilities, and personality qualities that may improve the ability of external auditors to identify fraud risk, the efficiency of fraud risk assessment was linked to digital technology abilities through the application of the partial least-squares structural equation model (PLS-SEM). The study [35] identified a positive correlation between fraud risk assessment and management and the efficient use of forensic accounting using chi-square, fisher test, and correlation, however, there is no relationship between fraud risk assessment and management in terms of techniques causing fraud.…”
Section: B Risk-based Methods Of Fraud Detectionmentioning
confidence: 99%
“…The study [33] uses the number of compromised records to determine the cost of a data breach; the findings indicate that the total number of affected records has a Fréchet distribution, random forest is used for estimating the number of such records. The study [34] uses the estimate of generalized extreme value parameters to evaluates competency, digital technology abilities, and personality qualities that may improve the ability of external auditors to identify fraud risk, the efficiency of fraud risk assessment was linked to digital technology abilities through the application of the partial least-squares structural equation model (PLS-SEM). The study [35] identified a positive correlation between fraud risk assessment and management and the efficient use of forensic accounting using chi-square, fisher test, and correlation, however, there is no relationship between fraud risk assessment and management in terms of techniques causing fraud.…”
Section: B Risk-based Methods Of Fraud Detectionmentioning
confidence: 99%
“…The methodologies also demonstrate the significance of individual variances and diverse cognitive approaches of auditors, which will be seen in the caliber of the audit outcomes . Due to the fast-paced advancements in information technology and the potential dangers associated with inaccuracies caused by computers, there is a growing necessity to enhance auditors' abilities in identifying fraud and significant mistakes (Ridzuan et al, 2022). The auditing literature reveals various elements that impact the quality of the auditor's report.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, AQ research in China was largely reliant on panel data of public accounting companies, and there was lack of empirical study in the country which directly gathered the perceptions of auditors concerning factors affecting AQ (Sun, 2017). External auditors are regarded as the primary line of defence for providing reasonable assurance that the financial statements are free from material misstatement, making their assessment of AQ crucial (Mat Ridzuan et al, 2022). Similarly, while previous research examined the effects of audit inspection on AQ, research that examined the effect of independent audit inspections on audit firms' QMS was limited.…”
Section: Introductionmentioning
confidence: 99%